Universal relations for compact stars with exotic degrees of freedom - Anil Kumar; Manoj Kumar Ghosh; Pratik Thakur; Vivek Baruah Thapa; Kamal Krishna Nath; Monika Sinha (European Physical Journal C: Particles and Fields, 2024)
Abstract The nature of the highly dense matter inside the supernova remnant compact star is not constrained by terrestrial experiments and hence modeled phenomenologically to accommodate the astrophysical observations from compact stars. The observable properties of the compact stars are highly sensitive to the microscopic model of highly dense matter. However, some universal relations exist between some macroscopic properties of compact stars independent of the matter model. We study the universal relation including the stars containing exotic degrees of freedom such as heavier strange and non-strange baryons, strange quark matter in normal and superconducting phases, etc. We examine the universal relations for quantities moment of inertia - tidal love number - quadrupole moment. We also study the correlation of non-radial f-mode and p-mode frequencies with stellar properties. We find the f-mode frequency observes the universal relation with dimensionless tidal deformability but the p-mode frequency does not show a good correlation with stellar properties. The p-mode frequency is sensitive to the composition of the matter. We find that universal relation is also applicable for stars with exotic matter in the core of the star with several models of exotic matter.